Legal Dynamics of Shari’ah Banking Dispute Resolution in Indonesia’s Religious Courts - Kusnoto, Kusnoto (Journal of Economicate Studies, 2025)
This research aims to describe the dynamics of dispute resolution by religious court judges in sharia banking legal cases. In this research method, the author uses qualitative research, with the research approach being an empirical juridical approach. The results of the research prove that the dynamics of law and its application by court judges in the Religious Court environment in resolving Sharia economic disputes are empirical legal dynamics that occur in Indonesia, where unlawful acts are related to sharia banking, which is regulated in Article 49 of Law No. . 3 of 2006 concerning Amendments to Law no. 7 of 1989 concerning Religious Courts, one of which is the authority of the Religious Courts to adjudicate sharia banking disputes. In resolving disputes, the Religious Courts use formal law and material law. Formal law in the form of procedures for resolving disputes is regulated by the Supreme Court Regulations and procedural law in the Civil Code. Meanwhile, material law is in the form of KHES, DSN-MUI Fatwa, Bank Indonesia Regulations, and Financial Services Authority Regulations and other statutory regulations. So the author found a pattern of resolving sharia banking disputes in the Religious Courts, discovered the factors causing sharia banking disputes and discovered the impact of verdicts on the development of the sharia economy.